QUEST FOR HAPPY LIFE IN MARIAH CAREY'S SONG LYRICS SOCIOLOGICAL APPROACH - KARTIKA , KALIS WINDA (2010)
This study deals with song lyrics sung by a phenomenal American singer, Mariah Carey. The objective of the study is to analyze Mariah Carey's song lyrics based on the structural elements and based on the sociological perspective. The type of data used in this study is text, namely the song lyrics. The data selection technique is thematic, namely based on the themes of the lyrics. The data collecting technique is note taking. The analysis of the data is descriptive. The result of the study is as follows. Firstly, based on the structural analysis, it is clear that Mariah Carey's song lyrics reflect a quest for happy life. Secondly, based on the sociological analysis, it is evident that Mariah Carey's song lyrics represent her social criticism against the American society that tends to move from the moral values